Following Interprofessional Education: Health Education Students’ Experience in a Primary Interprofessional Care Setting - Ghadir Fakhri Al-Jayyousi (14519192) (2021)
Background There is an accelerating need for interprofessional education (IPE) in the Public Health field, as healthcare providers become diverse and multi-disciplinary. Public Health students with health education concentration at Qatar University are required to join training sessions in IPE before the start of their field experience, where students are placed in a variety of community-based and clinical settings including, but not limited to, primary healthcare. Purpose The goal of this qualitative research study is to understand health education students’ experience in interprofessional care during their field experience in a primary healthcare setting and to highlight the successes and challenges. Patients and Methods Participants were third-year health education students (N = 22) enrolled in the Public Health program at Qatar University who obtained their experiential learning in three different primary health care centers. Students’ weekly reports reflecting on primary interprofessional care were included in the analysis for the purpose of this study. Following constant comparative techniques, thematic analysis was conducted on health education students’ reports. Results Interprofessional care was witnessed and practiced by students in teamwork and collaboration for the benefit of the patient, communication among health care professionals and referral process and patient flow. Health education students understood their role in interprofessional care in the fields of behavior change, and patient education and empowerment. However, professionals and patients were not recognizing health educators’ role and were not familiar with their contributions to interprofessional care in primary healthcare. Students suggested delivering interprofessional education for health care providers to enhance collaborative teamwork and promote knowledge about the evolving health education field among healthcare providers in Qatar. In addition, they recommended orienting their training supervisors about the goal of IPE-based practice in a primary healthcare setting. Conclusion Interprofessional care was observed and practiced by health education students through collaborative teamwork, communication among health care professionals and management of patient flow. However, they faced challenges during their practice-based IPE. The findings can be tailored towards planning for interprofessional education workshops to boost collaboration progress among health care providers including health educators and supporting professionals interested to implement practice-based IPE in their placement curriculums. Other Information Published in: Journal of Multidisciplinary Healthcare License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.2147/jmdh.s318110